Deciphering the synergistic mechanism of a novel flavonoid-antioxidant combination for asthma by combining systems pharmacology and experimental validation - Ziyi Chen; Xinling Ren; Xiaoyu Liu; Lifeng Tian; Yun Huang; Aiping Lyu; Wei Zhou (PLoS ONE, 2026)
Asthma is a multifaceted disorder characterized by an intricate interplay of various pathophysiological processes, including airflow obstruction, bronchial hyperresponsiveness, and underlying inflammation. This complexity encompasses a multitude of genetic, molecular, and environmental factors, making it challenging to identify effective strategies for prevention and treatment. Research into the pathogenesis and treatment of asthma continues in the pursuit of more comprehensive and targeted therapeutic approaches. The asthma pathology has been shown to be influenced by the flavonoid 7,4′- Dihydroxyflavone (74DHF), which is extracted from the herb Rhizoma Glycyrrhizae (Gancao), while taking the antioxidant ascorbic acid (VC) daily through food or supplements contributes to the treatment of asthma related to immunomodulatory regulation. However, the potential molecular or systemic mechanism of the combination of 74DHF and VC in treating asthma has yet to be fully understood, despite the demonstrated individual benefits of each compound. The present study employed a systems pharmacology strategy, combining target identification, network analysis, data integration, Gene Ontology (GO) enrichment analysis, pathway analysis, and in vitro experimental validation to uncover the synergistic pharmacological mechanisms of 74DHF-VC combination for asthma therapy. The results identified 153 and 308 targets for 74DHF and VC, 37 overlapping targets and 20 hub targets among 74DHF, VC, and asthma. Based on the GO and pathway analysis, 10 optimal common GO processes and 10 key canonical pathways were enriched, which were closely related to the combination therapy of 74DHF and VC against asthma. In addition, the in vitro experiments validated that 74DHF and VC had synergistic effects on anti-inflammation and fibrosis. The combined treatment reversed the LPS induced inflammation in macrophages and TGF-β induced cell migration and fibrosis in lung epithelial cells. The current study not only successfully explains the synergistic mechanisms underlying the efficiency of 74DHF and VC against asthma but also proposes a viable and promising strategy to fasten the process of combination treatment.